The secret to happiness [large type] - Fisher, Suzanne Woods (Fisher, Suzanne Woods. Cape Cod creamery, 2023)
"Fired from her dream job after making a colossal mistake, Calli Dixon's escaped to her aunt's home on Cape Cod for time to bounce back. Things go from bad to worse when Callie's cousin Dawn drags her to a community class about the secret to happiness. Happiness is the last thing Callie wants to think about right now, but instructor Bruno Bianco is relentless. He has a way of turning Callie's thoughts upside down. Her feelings, too. Bruno insists that hitting rock bottom is the very best place to be. But if that's true, how is it supposed to help her figure out what - or who - has been missing from her life all along?" --